A Preoperative Prediction Model for Lymph Node Metastasis in Patients with Gastric Cancer using a Machine Learning-based Ultrasomics Approach - Lin, Weiwei; Zhong, Qi; Guo, Jingjing; Yu, Shanshan; Li, Kunhuang; Shen, Qingling; Zhuo, Minling; Xue, EnSheng; Lin, Peng; Chen, Zhikui (Current Medical Imaging, 2024)
Objective This study aims to develop an ultrasomics model for predicting lymph node metastasis in patients with gastric cancer (GC). Methods This study enrolled GC patients who underwent preoperative ultrasound examination. Manual segmentation of the region of interest (ROI) was performed by an experienced radiologist to extract radiomics features using the Pyradiomics software. The Z-score algorithm was used for feature normalization, followed by the Wilcoxon test to identify the most informative features. Linear prediction models were constructed using the least absolute shrinkage and selection operator (LASSO). The performance of the ultrasomics model was evaluated using the area under curve (AUC), sensitivity, specificity, and the corresponding 95% confidence intervals (CIs). Results A total of 464 GC patients (mean age: 60.4 years ±11.3 [SD]; 328 men [70.7%]) were analyzed, of whom 291 had lymph node metastasis. The patients were randomly assigned to either the training (n=324) or test (n=140) sets, using a 7:3 ratio. An ultrasomics model that consisted of 19 radiomics features was developed using Wilcoxon and LASSO algorithms in the training set. Our ultrasomics model showed moderate performance for lymph node metastasis prediction in both the training (AUC: 0.802, 95% CI: 0.752-0.851, P<0.001) and test sets (AUC: 0.802, 95% CI: 0.724-0.879, P<0.001). The calibration curve analysis indicated good agreement between the predicted probabilities of ultrasomics and actual lymph node metastasis status. Conclusion Our study highlights the potential of a machine learning-based ultrasomics model in predicting lymph node metastasis in GC patients, offering implications for personalized therapy approaches.
Keywords: Lymph node metastasis